Synthesis And Characteristics Of Magnetic Hydrogels Prepared From Sawdust And Its Potential Application In Hydrogen Production - Idrus, Nurul Aina (Universiti Sains Malaysia, 2017)
As a clean energy carrier, hydrogen is expected to be one of the main energy sources in the 21st century and one of the candidates for an alternative energy carrier to replace fossil fuels. The basic aim of this study is to develop a feasible a new catalyst system for the hydrogen generation by catalytic hydrolysis of sodium borohydride, NaBH4. Sawdust-magnetic hydrogel (SD-MH) was prepared by a crosslinking procedure with cheap and environmentally friendly sawdust and iron salts. Sawdust which is a cellulose waste crosslinked with iron salts to form magnetic hydrogel will become the new alternative for hydrogen production. Cellulosic material is classified as cheap adsorbents because it can be obtained from various natural sources. In this study, catalyst amount, sodium hydroxide (NaOH) concentration, and the effects of temperature on the catalytic activity toward hydrogen production from hydrolysis of NaBH4 are completely investigated. It was found that the combination of 2.5wt% NaBH4 and 15wt% NaOH yields the highest performance for the hydrogen generation at 30°C with the lowest catalyst amount of 0.2g. The catalysts were characterized by Brunauer-Emmett-Teller Isotherm (BET), Fourier Transform Infrared Spectroscopy (FTIR) and Elemental Analysis techniques. BET study shows the surface area of magnetic hydrogel of 77.7311 m²/g. FTIR studies were carried out to understand the type of functional groups in sawdust responsible for the metal binding process while elemental analysis is done to study the composition elements in the prepared sawdust of different types.